Central Retinal Artery Occlusion after Phacoemulsification – Sight-threatening Complication - Manika Sharma; Kanav Gupta; Brij K. Gupta (Delhi Journal of Ophthalmology)
While peribulbar block is a safe modality, a relative risk of retinal vascular accident exists and its routine use should be done with caution. We report you a case of central retinal artery occlusion (CRAO) that occurred within 24 hours of routine uneventful phacoemulsification cataract surgery using peribulbar anaesthesia. A 55 year old man who underwent uneventful phacoemulsification cataract surgery using peribulbar lignocaine with hyaluronic acid and bupivacaine. Patient underwent routine phacoemulsification surgery of left eye for immature senile cataract with pterygium under peribulbar anaesthesia developed central retinal artery occlusion in the immediate post-operative period. The surgery was uneventful. CRAO is rare but an conciseness emergency seen after uneventful phacoemulsification and the cause is mainly anaesthesia related.